Pembuktian Perzinaan dalam Perceraian Menurut al-Qur’an dan Hukum Acara Perdata - Saadah, Mazroatus (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2014)
Abstract: This article highlights about adultery as one of the strong reasons of divorce. The reason is however quite difficult to be legally proved. As mentioned in the Quran, verification of adultery is by presenting the four male witnesses. And it has been mentioned in the Qurâan chapter al-Nisa, verse 15, 16, 25 and in chapter al-Nur, verse 2, 4, 13 that the four male witnesses should be Muslim. In addition, Another way to prove adultery is lian as written in the Quran, chapter al-Nur, verse 6-9 that a husband who accuses his wife committing adultery while he does not have adequate evidence other than he himself, so he can prove it with a lian oath. It is also clearly stipulated in article 88 of Undang-Undang No.7 tahun 1989. While the proofs of adultery under the civil law of Religious Court other than the testimony of the four male witnesses are also by letter, oath, recognition, and conjecture. Keywords: Verification, adultery, the Quran, the civil law